PENERAPAN SISTEM INFORMASI MANAGEMENT WAREHOUSE DAN MULTI OUTLET BERBASIS TEKNOLOGI HYBRID PADA CINDY THE SMILLING GIFT SHOP JAKARTA - Ivan Ismail; Muryan Awaludin (CKI ON SPOT, 2017)
Design a Management Warehouse Information System and Multi Outlet Based Hybrid Technology at Cindy The Smilling Gift Shop Jakarta. Cindy The Smilling Gift Shop is a company engaged in the retail souvenirs who make transactions directly. The company was built in 1998 and has branches in several cities including Jakarta, Bandung, Purwokerto, Yogyakarta, Solo and Surabaya. To improve efficiency in working, Cindy The Smilling Gift Shop performs improvement process to achieve work efficiency. One effort is to design and build a warehouse management information system and multi outlets. In the system before the repair is done, the process of reporting the sale and the process of updating the stock of goods at the outlet still using manual way that takes 3 days to 1 week, so the process is not efficient and real time. Then after the development of warehouse systems and multi outlets, the process of reporting and selling stock updates can be done in real time, because it is integrated with applications connected to the Internet network. So that can do efifiesnsi time up to 72 hours or if in conversion with operational cost can reach Rp. 1.260.000, -.